2017
DOI: 10.1177/0284185117738547
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum hemorrhage from non-uterine arteries: clinical importance of their detection and the results of selective embolization

Abstract: Background Identification of the source of postpartum hemorrhage (PPH) is important for embolization because PPH frequently originates from non-uterine arteries. Purpose To evaluate the clinical importance of identifying the non-uterine arteries causing the PPH and the results of their selective embolization. Material and Methods This retrospective study enrolled 59 patients who underwent embolization for PPH from June 2009 to July 2016. Angiographic findings and medical records were reviewed to determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…4 Among previous articles, there were only two reports of cases that demonstrated the need for OAE accompanied by UAE for controlling severe PPH. 10,11 Our study suggested that the necessity of OAE for patients who were supposed to have the blood from ovarian artery to uterus and this was one finding of this study.…”
Section: Discussionsupporting
confidence: 58%
“…4 Among previous articles, there were only two reports of cases that demonstrated the need for OAE accompanied by UAE for controlling severe PPH. 10,11 Our study suggested that the necessity of OAE for patients who were supposed to have the blood from ovarian artery to uterus and this was one finding of this study.…”
Section: Discussionsupporting
confidence: 58%
“…The ovarian artery supplied only small part of RPOC on angiography and both uterine artery embolization was enough to stop bleeding caused by RPOC. However, ovarian arteries might be one of the causes of re-bleeding: ovarian artery supply was confirmed in 12% of PPH patients (Kim et al, 2018). Therefore, it is suggested that we should visualize both ovarian artery on initial aortography at the level of the renal arteries and selective embolization might be needed if its contribution to bleeding is confirmed (Kim et al, 2018;Maassen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous round ligament hematoma is an extremely rare cause of acute pelvic pain in adult female patients [3] , [4] , [5] and, to the best of our knowledge, such a case has never been reported in the medical literature for the paediatric population.…”
Section: Introductionmentioning
confidence: 90%